Spatial management of recyclable material collection routes with GIS support and productivity indicators - Da Cunha e Silva, Darllan Collins [UNESP]; Nery, Liliane Moreira [UNESP]; Simonetti, Vanessa Cezar [UNESP] (Univ Tecnologica Fed Parana-utfpr, 2023)
Increased production of municipal solid waste is a recurring problem for public managers, studies are needed that contemplates its management and methodologies to optimize collection routes. Therefore, this study aims to map the selective collection routes and identify opportunities for improvement through quantitative indicators of collected material and geotechnologies. Therefore, a survey was made of the amount of recyclable material collected per stretch travelled, analysed route performance, proposed minimizing unproductive routes, and suggested new routes with high potential of recyclable material collection. Results showed that the route management provided an increase of 2.75 tons per month of recyclable waste and a collection of R$ 2,777.96/month evidencing the importance of spatial analysis as a solid waste management tool for recycling cooperatives.
Keywords: Geoprocessing; Cooperative; Solid waste; Selective collection